Association of lipid accumulation product and visceral adiposity index with metabolic syndrome in euthyroid population - Jie-wu HUANG; Dong-ting WU; Jia-yi SONG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo investigate correlations of lipid accumulation product (LAP) and visceral adiposity index (VAI) with metabolic syndrome (MS) and to evaluate values of LAP and VAI in MS diagnosis for providing references to early diagnosis of MS in euthyroid population. MethodsTotally 800 adult volunteers (≥ 18 years) were recruited with stratified sampling at eight communities in four districts of Shenzhen city, Guangdong province. A questionnaire interview, physical examination, thyroid B-ultrasonography and laboratory test were conducted among the volunteers simultaneously from October 2018 through January 2019. In this analysis, the values of LAP and VAI were calculated for 344 participants with normality of thyroid B-ultrasonography and thyroid function. The linear trend chi-square test, unconditional multivariate logistic regression and receiver operator characteristic (ROC) curve were used to assess associations of LAP and VAI and MS among the euthyroid participants. ResultsOf the all euthyroid participants, 112 (35.5%) were identified with MS. For the participants with the LAP and VAI values within the lowest, 2nd, 3rd, and the highest quartile, the detection rate of MS were 4.7% and 9.2%, 15.1% and 19.8%, 50.0% and 45.9%, and 72.1% and 67.4%, respectively; both LAP and VAI showed significantly positive correlation with MS prevalence (both P trend < 0.05). After adjusting for confounders such as sex, age, education, smoking, alcohol drinking, body mass index (BMI), central obesity, hypertension, fasting plasma glucose (FPG), total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), creatinine (Cr), serum uric acid (SUA) and SUA/Cr, the results of unconditional multivariate logistic regression analysis demonstrated that the participants with the LAP values within the 2nd and 3rd quartile were at an increased risk of MS (odds ratio [OR] = 3.48, 95% confidence interval [95% CI]: 1.30 - 9.31 and OR = 3.80, 95% CI: 1.26 - 11.46) compared with those with the values within the lowest quartile; the participants with the VAI values within the 2nd quartile were also at an increased risk of MS (OR = 2.79, 95% CI: 1.13 - 6.87) in comparison with those with the values within the lowest quartile. The area under ROC curve (AUC) of BMI, waist circumference (WC), SUA/Cr, LAP and VAI for MS prediction were 0.74, 0.83, 0.59, 0.84 and 0.79, respectively, indicating a higher effectiveness of LAP than that of BMI, SUA/Cr and VAI, and a higher effectiveness of VAI than SUA/Cr for MS prediction (all P < 0.01). ConclusionBoth elevated LAP and VAI could increase the risk of MS in euthyroid population. The results suggest a potential combined application of LAP and VAI in MS early detection, intervention, and precision treatment.